Comparing the Different Behavioral Outcomes of Extremism: A Comparison of Violent and Non-Violent Extremists, Acting Alone or as Part of a Group. (3rd August 2022) - Knight, Sarah; Keatley, David; Woodward, Katie
Abstract: Presented here is an exploratory study that compared four kinds of extremists (violent lone, nonviolent lone, violent group member, and nonviolent group member). Thematic analysis of 40 case studies identified five key themes and a number of subthemes that comprised a range of underlying variables. Comparisons of the four groups showed that in many ways violent and nonviolent extremists acting alone or as part of a group do not differ. However there were some variables that distinguished between groups. Findings are discussed in terms of implications for countering and preventing violent extremism.